Por dentro da história: mulheres operosas no mundo do comércio em Parnaíba (1930 a 1950) - Tourinho, Mary Angélica Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
I present in this work women among the productive activities in the world of commerce of the city of Parnaíba-PI, from 1930 to 1950, relying on diversified documentation, mainly the Almanac of Parnaiba, memoir writers, interviews, newspapers and a theoretical framework that favors the study of daily life, gender, the discourse analysis and the evidential paradigm. During this period have widened the urban transformations, coming from the local economic growth; these urban changes and the influences that were processed at the international and national levels, interfered in the city daily life, changing his appearance and behavior order, which reached women, especially those who might have access to the tools provide by these changes, including work, leisure and education; also increase the survival chance of then, due to the expansion of workspaces, both formal and informal, including women of the most diverse social groups. Amid this context, we present the city as a reproducer of institutional discourses that have developed as representatives of civility and modernity who understood the responsible motherhood, imparting of a healthy childhood as essential for the good of the state, these speeches were at the base of the projects established in the period in which Getúlio Vargas headed the power of Brazil. Allusions to the women work, the dangers, the rights and education, were disseminated through newspapers and almanacs responsible for the movement of values which concentrated on the local society and, more specifically, on women; is analyzed in this work the speeches directed to women and discourses produced by them, as well as the effective forms of work, formal and informal, putting women as the featured subject in this approach, finally, we present and analyzed spaces occupied by them and how were distributed, with their respective activities by the city of Parnaíba, demonstrating...

Apresento neste trabalho, mulheres em meio às atividades produtivas, no mundo do comércio da cidade de Parnaíba-PI de 1930 a 1950, apoiando-nos em documentação diversificada, principalmente o Almanaque da Parnaíba, memorialistas, entrevistas, jornais e um referencial teórico que privilegia o cotidiano, o gênero, a análise do discurso e o paradigma indiciário. Neste período, acentuaram-se as transformações urbanísticas, advindas do incremento econômico local, alavancado pelo crescimento das exportações dos produtos regionais que ganhavam espaço no mercado mundial. Estas mudanças urbanísticas e as diversas influências que se processavam em âmbito internacional e nacional, interferiram, sobremaneira, no cotidiano da cidade, alternando-lhe feições de ordem estética e comportamental, que atingiram mulheres, principalmente as que podiam ter acesso aos espaços facultados por essas mudanças, incluindo-se aí o trabalho, o lazer e a instrução; que aumentaram-lhes as possibilidades de sobrevivência, devido à ampliação dos espaços de trabalho, tanto formais, quanto informal. Dessa forma, mulheres de diversificados meios sociais têm mais possibilidades de adentrarem no mercado de trabalho. Em meio a esse contexto, apresenta-se a cidade com os diferentes sujeitos sociais, e ainda como repositório de discursos institucionais que se desenvolveram, ou se afirmaram como modelo de civilidade e modernização; imbuídos de referenciais patrióticos e um ideário que privilegiava uma maternidade responsável, proporcionadora de uma infância saudável, fundamental para o bem do Estado. Estes discursos estavam na base dos projetos instituídos no período em que Getúlio Vargas esteve à frente do poder do Brasil. Alusões ao trabalho, formal e informal, aos seus perigos, direitos e deveres, à instrução, a circulação dos valores e regulações que incidiam de forma mais evidente sobre...
Keywords: Trabalho feminino; Mulheres; Parnaíba (PI) História; Parnaíba (PI) - Comércio; Women employees